Konflik Batin Tokoh Utama dalam Novel Bibi Gill Karya Tere Liye Kajian Psikologi Sastra - Agnes Apryliana; Helmi Seftiani; Dini Nurhayati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Literary works are artistic representations of actual human existence that do not aim to provide knowledge. One way to express people's lives is through sistra works. The novel Bibi Gill by Tere Liye is the data source for this research. Documentation is the data collection method used by researchers in this investigation. Three (3) methods were used in the data collection process using this documentation: literature review, reading strategies, and note taking. The results of the research showed that there was inner conflict experienced by the main character in the novel Bibi Gill. there are changes in the psychology of Bibi Gill as the main character which is influenced by other characters and the environment.